2019
DOI: 10.1080/15374416.2019.1614002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Family Accommodation of Childhood Anxiety: Confirmatory Factor Analysis, Validity, and Reliability of the Parent and Child Family Accommodation Scale – Anxiety

Abstract: Objective: Research on family accommodation is burgeoning, implicating it in the development, maintenance, and treatment of childhood anxiety. Additional data are needed to guide theory development and clinical application in this area. The factors underlying family accommodation measures have never been confirmed, nor have any test-retest data been reported. The study's objectives were to provide confirmatory data of the factorial structure and the first test-retest reliability data on the most widely used me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Our factor analysis confirmed that the Chinese FASA-AR comprised two correlated factors: participation in symptomrelated behaviors and modification of functioning. Previous findings (Lebowitz et al, 2013(Lebowitz et al, , 2019 differed on which latent factor item 5 (avoiding doing things, going places or being with people because of the symptoms) loaded. Our results supported the model distributing this item to the modification of functioning factor (Lebowitz et al, 2019).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Our factor analysis confirmed that the Chinese FASA-AR comprised two correlated factors: participation in symptomrelated behaviors and modification of functioning. Previous findings (Lebowitz et al, 2013(Lebowitz et al, , 2019 differed on which latent factor item 5 (avoiding doing things, going places or being with people because of the symptoms) loaded. Our results supported the model distributing this item to the modification of functioning factor (Lebowitz et al, 2019).…”
Section: Discussionmentioning
confidence: 71%
“…The main differences between the two scales are that the FASA is reported by accommodators, i.e., parents of anxious children, while the FASA-CR is reported by anxious children themselves. Both scales established two related PAR and MOD factor structures, with evidence of good psychometric properties including internal consistency, convergent and divergent validity, and test-retest reliability (Lebowitz et al, 2019). In addition, the factor structures and psychometric properties of the FASA were previously identified on a crosscultural sample of accommodators from the United States and Israel (Lebowitz et al, 2013), supporting the potential of the cross-cultural properties of FASA and FASA-CR.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations